Improvement of Children’s Negative Psychology Based on Cooperative Learning - Weiting Jiao; Zhimei Xue; Liying Wang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This paper introduces structural equation model (SEM) to study the improvement of children’s negative psychology through cooperative teaching of PE, and analyzes the interaction effect, regulation effect, and mediating effect involved in the problem. Next, the proposed SEM was reconstructed into a self-organizing path constrained neural network (SOPCNN), and the results of latent variables and observable indices were aggregated. Experimental results show that the application of cooperative teaching in PE can effectively improve the negative psychology of children. The research results provide a good reference and facilitate the practical research of improving children’s negative psychology through cooperative learning.